Kognitif Moral dalam Upaya Pembangunan Emotional Intelligence Siswa Sekolah Dasar - Yesi Anita; Rafhi Febryan Putera; Hasmai Bungsu Ladiva (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2020)
Moral cognitive-based learning as an effort to develop elementary school student emotional intelligence needs to be realized in the real life of students to face developments in science and technology. The purpose of this study was to describe the importance of moral cognitive-based development as an effort to develop elementary school student emotional intelligence. The method used is descriptive qualitative. The results showed that, in an effort to develop emotional intelligence, elementary school students need to be given moral cognitive in the learning process in the classroom.